Prevalence of Cardiac Risk Factors and Attitude toward Self-Risk Assessment among Cardiac Care Givers - Shumaila Furnaz; Musa Karim; Sajjad Ali; Muhammad Tanzeel ul Haque; Muhammad Abdullah Usman; Dileep Kumar; Tariq Jamal Siddiqi; Khawar Abbas Kazmi (SAGE Publishing, 2020)
Objective: Aim of this survey was to assess the prevalence of cardiovascular diseases (CVD) risk factors and attitude toward self-risk assessment among cardiac care physicians (who did not have CVD history), at a tertiary care cardiac center in Pakistan. Design: In this survey we included cardiac care givers who had a minimum of 1 year of working experience in a cardiac care center. Participants: Participants with self-reported history of established diagnosis of CVD were excluded. Face-to-face interviews were conducted with the help of a structured questionnaire which consisted of demographic information, data regarding established CVD risk factors, self-awareness, and attitude toward CVD risk assessment. Results: A total of 126 participants were interviewed, out of which 20.6% (26) were females and mean age was 36.1±7.6 years. The most prevalent CVD risk factor was family history of CVD (33.3%) followed by smoking (14.3%) and 23.8% had body mass index of ≥27.5 kg/m 2 . Around 23% of the participants did not know their cholesterol levels, similarly more than 74% were not aware of their high-density lipoproteins levels. More than 76% had never assessed their CVD risk and more than 37% don't know or don't have any opinion about their own CVD risk. Conclusions: The present study reveals low prevalence of conventional cardiac risk factors and marginally higher tendency of modifiable risk factors, such as smoking and obesity, among the cardiac physicians. A large proportion of these cardiac physicians have not yet assessed their CVD risk.